The Circular Economy in Europe: Critical Perspectives on Policies and Imaginaries - Kovacic, Zora; Strand, Roger; Völker, Thomas (Routledge Explorations in Sustainability and Governance, 2020)
The Circular Economy in Europe presents an overview and a critical discussion on how circularity is conceived, imagined, and enacted in current EU policy-making. In 2013, the idea of a circular economy entered the stage of European policy-making in the efforts to reconcile environmental and economic policy objectives. In 2019 the European Commission declared in a press release that the Circular Economy Action Plan has been delivered. The level of circularity in the European economy, however, has remained the same. Bringing together perspectives from social sciences, environmental economics and policy analysis, The Circular Economy in Europe provides a critical analysis of policies and promises of the next panacea for growth and sustainability. The authors provide a theoretical and empirical basis to discuss how contemporary societies conceive their need to re-organise production and consumption and explores the messy assemblage of institutions, actors, waste streams, biophysical flows, policy objectives, scientific disciplines, values, expectations, promises and aspirations involved. This book is essential reading for all those interested in understanding how ideas about the circular economy emerged historically, how they gained traction and are used in policy processes, and what the practical challenges in implementing this policy are.